The Relationship Between Sedentary Lifestyle and Obesity in Children at Majalengka Wetan VII Elementary School - Irawan, Ade Tedi; Siti Nuryawati, Lina; Dwiyana, Prizas (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Sedentary Lifestyle is defined as a lifestyle characterized by a lack of physical activity. Based on data from the Indonesian Health Survey (SKI), the issue of overweight among children aged 15-12 years in Indonesia remains quite high. The national prevalence of overweight is 11.9%, and obesity reaches 7.8%. Children’s current lifestyle resembles a sedentary lifestyle, where activities are done with minimal energy expenditure. A sedentary lifestyle can negatively impact health, including increasing the risk of obesity due to an imbalance between calorie intake and energy expenditure. Objective. This study aims to determine the relationship between sedentary lifestyle and obesity in school children at SDN Majalengka Wetan VII in 2024. This research uses a quantitative correlational approach and a cross-sectional method. Data on dependent and independent variables were collected at the same point in time to determine if there was a relationship or association between the variables. Primary data were obtained through structured questionnaires using the ASAQ and measurements of weight and height to assess obesity incidence based on the Z-Score. The results of the Chi-Square statistical test showed a p-value of 0.000, smaller than α = 0.005, meaning that Ha is accepted and H0 is rejected. It can be concluded that there is a significant relationship between sedentary lifestyle and obesity in children at SDN Majalengka Wetan VII in 2024. It is suggested that children increase daily physical activity, such as playing outdoors or participating in sports, reduce excessive sitting time, and limit the use of electronic devices to avoid obesity.